Matched development of a pair of monozygous twins of grossly different size at birth. Issue 6 (June 1974) - Buckler, J. M. H.; Robinson, A.
Abstract : Monozygous twins had birthweights differing by 1·64 kg. The smaller twin, only 45% of her sister's weight, rapidly caught up, and at the age of 10 years physical growth was similar and there was negligible difference in their intelligence and educational attainment.